Collaborative Pentahelix Governance and Environmental Literacy Development in Mangrove Ecotourism - Yunus Winoto; Asep Saeful Rohman; Saleha Rodiah; Falih Ijlal Septian; Farrah Diana Saiful Bahry (Jurnal Ilmiah Peuradeun, 2026)
Despite the ecological value of mangrove ecotourism, environmental degradation due to waste accumulation and intense anthropogenic pressures remains a critical challenge in Karangsong Beach, Indonesia. While the Pentahelix model is recognized for destination management, its potential as a pedagogical tool for behavioral change remains underexplored. This study investigates how the Pentahelix synergy fosters comprehensive environmental literacy. Employing a qualitative case study through interviews, observations, and document analysis, the findings reveal that synergy enhances awareness through functional roles: academics provide scientific validation, the private sector provides vital funding and infrastructure, the government ensures regulation, the community leads operations, and the media amplifies educational narratives. Crucially, this study reconceptualizes collaboration as a structured “pedagogical mechanism” that transforms abstract ecological knowledge into practical conservation behavior. This research presents the “Karangsong Model” as a scalable governance framework for the Global South, demonstrating that long-term, sustainable conservation requires a hybrid architecture that seamlessly integrates economic incentives and educational responsibilities.